Pengaruh Variasi Pencampuran Tepung Kacang Hijau (Phaseolus Radiatus) Pada Pembuatan Brownies Singkong Kukus Terhadap Sifat Fisik, Sifat Organoleptik, Dan Kadar Protein - Diah Ruhutami; Setyowati Setyowati; Farissa Fatimah (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2018)
Wheat flour and rice flour mostly used to produce local food — nutrition content in cassava flour the same as wheat flour. Cassava flour can substitute wheat flour. Green bean flour has a high protein content as 22,9%. Mixing green bean flour (Phaseolus radiatus) in cassava brownies steamed can increase the protein content. This research was aimed to determine the effect of variation mixing green bean flour (Phaseolus radiatus) in cassava brownies steamed on physical properties, organoleptic characteristics and protein content. This research used semi experiment design with the random design group. Kruscal walls and Anova one way were used for organoleptic data characteristics. LSD test was used for protein content. Physical properties were done by the researcher, the organoleptic characteristic was done by semi-trained panellists and protein content was done in the laboratory. The result was variation mixing green bean flour (Phaseolus radiatus) gives effect on physical properties (taste and flavour) and protein content (p<0,05). Mixing green bean flour in cassava brownies steamed did not give effect on organoleptic characteristics (p>0,05). The conclusion was variation mixing green bean flour (Phaseolus radiatus) gives effect on physical properties and protein content but did not give an effect on organoleptic characteristics.